2017
DOI: 10.1038/onc.2017.385
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of androgen receptor-regulated lipid biosynthesis drives the progression of castration-resistant prostate cancer

Abstract: Androgen receptor (AR) is a transcriptional activator that in prostate cells stimulates gene expression required for various cellular functions, including metabolisms and proliferation. AR signaling is also essential for the development of hormone-dependent prostate cancer (PCa) and its activity can be blocked by androgen deprivation therapies (ADTs). Although PCa patients initially respond well to ADTs, the cancer inevitably relapses and progresses to lethal castration-resistant prostate cancer (CRPC). Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 48 publications
3
70
0
Order By: Relevance
“…In view of the relationship between androgens and lipid metabolism, several studies have reported that genes mediating the lipogenesis pathway ( i.e. FASN , SREBP1 ) that were initially suppressed following castration were subsequently up-regulated or re-activated during the emergence of CRPC [ 70 , 118 , 124 ]. Indeed, AR-mediated lipogenesis is a highly-conserved metabolic feature of CRPC ( Fig.…”
Section: Effects Of Adt On Lipid Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the relationship between androgens and lipid metabolism, several studies have reported that genes mediating the lipogenesis pathway ( i.e. FASN , SREBP1 ) that were initially suppressed following castration were subsequently up-regulated or re-activated during the emergence of CRPC [ 70 , 118 , 124 ]. Indeed, AR-mediated lipogenesis is a highly-conserved metabolic feature of CRPC ( Fig.…”
Section: Effects Of Adt On Lipid Metabolismmentioning
confidence: 99%
“…Indeed, AR-mediated lipogenesis is a highly-conserved metabolic feature of CRPC ( Fig. 1 ), suggesting the potential of lipid metabolism as a key survival pathway that promotes resistance [ 124 ].…”
Section: Effects Of Adt On Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence shows that the lethal PCa is associated with deregulation of lipid or cholesterol biosynthesis (20 -23) and that lipid biosynthesis induced by AR reactivation can induce resistance to androgen-deprivation therapy and contributes to CRPC progression (24). For enzalutamide resistance, cholesterol is capable of participating in intracrine androgen biosynthesis, conferring PCa cells with resistance to enzalutamide (7).…”
Section: Simvastatin Overcomes Enzalutamide Resistancementioning
confidence: 99%
“…MBOAT2 has rankings in both the AR-Hs-All TC (CPV = 3.7E-38, 99.96 th percentile) and ChIP-Seq (99 th percentile) consensomes comparable to those of canonical AR target genes such as KLK3 and TMPRSS2. In contrast to the large volume of literature devoted to these targets however, with the exception of a mention in a couple of androgen expression profiling studies 13,14 , the functional role of MBOAT2 in the context of AR signaling has been entirely unstudied. In validation of its elevated AR consensome ranking, we confirmed that MBOAT2 was an ARregulated gene in cultured prostate cancer cell lines (Fig.…”
Section: Bench Validation Use Case 1: Elevated Consensome Rankings Prmentioning
confidence: 99%